No Stents, No Bypass Surgery: A Cultural Shift Toward Drug-Coated Balloons in Indonesia - Mulijono, Dasaad (Cardiology and Cardiovascular Medicine, 2025)
In many Southeast Asian countries, including Indonesia, there is a notable cultural reluctance toward invasive cardiovascular procedures such as coronary artery bypass grafting (CABG) and the implantation of permanent foreign bodies like coronary stents. Beyond this cultural aversion, drugcoated balloon (DCB) technology offers distinct clinical advantages over drug-eluting stents (DES), including eliminating permanent implants, preserving vascular integrity, and reducing the need for prolonged dual antiplatelet therapy. In recent years, the clinical indications for DCB use have expanded significantly now encompassing not only in-stent restenosis (ISR) and small vessel disease but also de novo lesions of all sizes, acute myocardial infarction, left main and ostial lesions, bifurcation lesions, chronic total occlusions, long and diffuse disease, heavily calcified lesions, vulnerable plaques, and patients at high bleeding risk or with anticipated noncompliance. This article examines the sociocultural and clinical factors driving the adoption of DCB technology. It highlights our experience at the Cardiac Centre of Bethsaida Hospital, pioneered by Prof. Dasaad Mulijono, where the integration of DCB interventions with a plant-based diet (PBD) program has resulted in restenosis rates as low as 2%—a stark contrast to the 10–20% commonly reported at other centres. We also present evidence from computed tomography coronary angiography (CTCA) and coronary angiography demonstrating atherosclerosis regression in patients adhering to the PBD approach. Given the proliferation of unproven and potentially harmful therapies, such as chelation therapy, enhanced external counterpulsation (EECP), and unvalidated thrombectomy techniques, knowledgeable and dedicated physicians must proactively educate patients about evidence-based treatment options. Furthermore, integrating artificial intelligence (AI) presents a transformative opportunity to personalize patient education, enhance clinical decision-making, and guard against misinformation and medical fraud. As the landscape of coronary artery disease (CAD) management continues to evolve, the appropriate utilization of DCB technology, combined with patient-centred education and holistic care models, represents a critical step forward in improving cardiovascular outcomes across diverse populations.